There's more to crypto than currency. - McCormick, Packy (Economist)
The article informs on the future of blockchains. It mentions at the core of this expansion was a new concept, non-fungible tokens (NFTS), these are blockchain-based records that uniquely represent items of digital media, including art, videos, music, games, text and code, meanwhile, blockchains can support a lot more applications beyond money and finance.